The History of the Liturgical Use of the "Professio fidei" in the Hispanic Mass - Celiński, Łukasz (Verbum Vitae, 2025)
The Hispanic Mass was the first among all Western liturgical traditions to welcome the Symbol of Faith within the ritual sequence. The Professio fidei, still present in the rite of the Hispanic-Mozarabic Mass, renewed after the Second Vatican Council, is characterized not only by the retention of the plural at the beginning (Credimus in place of Credo known in the Roman rite), corresponding to the conciliar text, but also by its specific ritual placement, before the prayer of the Our Father. The present contribution, beginning with a critical study of the sources, offers a historical look at the genesis and development of the liturgical use of the Symbol of Faith in the Hispanic Mass. Based on the insights of the methods of comparative liturgy it also intends to offer a broader context of the process of the evolution of liturgical rites. The study conducted with scientific criteria was also able to challenge, among other things, the idea of the ordinary presence of the Professio fidei in the history of the Hispanic Mass from the time of its appearance toward the end of the 6th century.